Aplikasi Metode Tanam Dan Pemberian Pupuk Organik Cair Serta Pengendalian Hama Dan Penyakit Terhadap Parameter Agronomis Dan Lingkungan Pada Tanaman Padi Sawah Di Lahan Pasang Surut - Khafid Zulistiawan; Salamiah Salamiah; Emmy Sri Mahreda; Zainal Abidin (Universitas Lambung Mangkurat, 2020)
The planting method is a technological innovation in increasing rice production. Increase rice productivity by changing the management of plants, soil, water and nutrients, increasing population and optimizing growth space for plants. This study will examine the use of three planting methods (SRI, jajar legowo and Hazton), with three applications of liquid organic fertilizer and application of vegetable pesticides. The results showed that the Hazton method with the application of liquid organic fertilizer from livestock manureproduced the highest plant height and the highest number of roots when applied with botanical pesticides compared to other treatments (SRI and jajar legowo).